2015
DOI: 10.2308/bria-51183
|View full text |Cite
|
Sign up to set email alerts
|

The Joint Effect of Unfavorable Supervisory Feedback Environments and External Mentoring on Job Attitudes and Job Outcomes in the Public Accounting Profession

Abstract: Unfavorable supervisory feedback environments (SFEs) occur when supervisors provide unhelpful, inconsistent, and inconsiderate feedback. This study investigates whether external mentoring (i.e., mentoring support that is provided by a superior who is external to the supervisor-subordinate relationship) can moderate (i.e., attenuate) the adverse effects of unfavorable SFEs that occur in the accounting profession. Based on a survey of 421 public accounting professionals, the results indicate that unfavorable SFE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 72 publications
1
22
0
Order By: Relevance
“…Those experiencing a positive feedback environment are unlikely to have intentions of quitting their current job (Sparr & Sonnentag, 2008). Further, both the quality of feedback and favorable feedback subscales of the feedback environment scale (Steelman et al, 2004) were negatively related to turnover intentions in nurses (Van Waeyenberg, Decramer, & Anseel, 2015), accountants (Dalton, Davis, & Viator, 2015), and across multiple industries (Sparr & Sonnentag, 2008). This body of evidence serves as the basis for our prediction that there is a positive relationship between feedback environment and intent to continue the working relationship with a faculty research advisor.…”
Section: Feedback Environmentmentioning
confidence: 89%
“…Those experiencing a positive feedback environment are unlikely to have intentions of quitting their current job (Sparr & Sonnentag, 2008). Further, both the quality of feedback and favorable feedback subscales of the feedback environment scale (Steelman et al, 2004) were negatively related to turnover intentions in nurses (Van Waeyenberg, Decramer, & Anseel, 2015), accountants (Dalton, Davis, & Viator, 2015), and across multiple industries (Sparr & Sonnentag, 2008). This body of evidence serves as the basis for our prediction that there is a positive relationship between feedback environment and intent to continue the working relationship with a faculty research advisor.…”
Section: Feedback Environmentmentioning
confidence: 89%
“…This study is an initial examination of abusive supervision, voicing, and mentoring in a professional context. Prior research investigating mentors and abusive supervision in accounting used survey based approaches (e.g., Dalton et al, 2015). To capture the specific constructs and their causal inferences, I isolate abusive supervision, voicing, and mentoring using an experimental methodology, which is appropriate to maintain internal validity regarding the assertions about the dependent and independent variables (Pedhauzer & Schmelkin, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…They chronicle how a mentor can help advance a protégé within the firm, making the protégé more visible to superiors. Dalton, Davis, and Viator (2015), found that having a mentor reduced the negative effects of unfavorable supervisory feedback in public accounting firms. Considering the extant research on abusive supervision, voicing, and mentoring, I arrived at the following research question: Does a mentoring relationship assist a protégé to voice in an adverse situation with an abusive supervisor?…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially trust is a key factor that increases the quality of the relationship, as it reassures the subordinate that the supervisor is acting in his best interest (Brower et al 2000). The formation of high quality relationships is crucial to create a positive feedback environment that encourages the subordinate to follow the supervisor's advice and feedback to develop further (Dahling et al 2012;Dalton et al 2015). Trust has also been associated with lower knowledge transfer costs and a higher probability that subordinates understand and are able to apply the transferred knowledge (Levin and Cross 2004;Tsai and Ghoshal 1998;Zaheer et al 1998), all related to the main responsibilities of the supervisor.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%